Analysis of viral quasispecies by NGS technologies: quasiflow - Díaz-Martínez, Luis; Seoane Zonjic, Pedro; Claros-Díaz, Manuel Gonzalo; Viguera-Mínguez, Enrique; Grande-Pérez, Ana (Sociedad Española de Virología, 2017)
We have developed QuasiFlow, a workflow designed in AutoFlow that takes advantage of NGS technologies to reconstruct quasispecies based in Illumina reads. QuasiFlow characterises and computes several key parameters, such as recombination events, SNPs, transitions, transversions, indels, quasispecies reconstruction, normalized Shannon index, nucleotide diversity and mutation networks. Moreover, it performs a comparative study of the samples comprising correlation, ANOVA and PCA analyses of the previously obtained virus population parameters. Using QuasiFlow we have analysed Illumina MiSeq reads from DNA samples obtained in mixed infections of ssDNA begomovirus in tomato plants amplified by rolling circle amplification. Further, we have extended the use of QuasiFlow to the analysis of the highly variable mitochondrial DNA. For that, we have used DNA Illumina MiSeq reads from 47 human mitochondrial samples from different cell lines obtained from the NCBI SRA database
Keywords: Bioinformática; Bioinformatic